A Novel Technique for Solving Multiobjective Fuzzy Linear Programming Problems - Hamadameen, Abdulqader O. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2017)
This study considers multiobjective fuzzy linear programming (MFLP) problems in which the coefficients in the objective functions are triangular fuzzy numbers. The study proposing a new technique to transform MFLP problems into the equivalent single fuzzy linear programming problem and then solving it via linear ranking function using the simplex method, supported by numerical example.